Enhanced Load-Aware Handover Algorithm for High-Density IEEE 802.11 ESS Networks - Derrick Qin Sheng, Wong; Chong Eng, Tan (ECTI Association, Thailand, 2025)
High-density Wi-Fi networks, particularly in Extended Service Set (ESS) environments, frequently experience performance degradation due to sub-optimal handover mechanisms that rely exclusively on Received Signal Strength Indicator (RSSI). Such approaches often lead to traffic imbalance, increased packet loss, and reduced Quality of Service (QoS). This paper introduces a novel implementation of a load-aware handover strategy that integrates both RSSI and real-time access point (AP) load metrics to optimize handover decisions. Through its adaptive weighting function and penalty mechanism, ELAHA dynamically balances signal strength with AP load conditions, achieving improved network efficiency and user experience in dense deployment scenarios. Results demonstrate that ELAHA significantly outperforms the conventional RSSI-Based Algorithm (RBA), achieving lower latency, reduced jitter and packet loss, decreased handover frequency, and enhanced overall throughput. These findings highlight ELAHA's potential as a robust and scalable solution for maintaining consistent QoS in high-density Wi-Fi networks.